2017
DOI: 10.1126/sciadv.1601833
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated molecular changes are deleterious and may modulate life span through diet

Abstract: Age-associated molecular changes are deleterious and causally linked with aging and may affect life span through diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Our study includes 77 samples with ages between 60 and 99 years, 19 of them older than 90, thus providing substantial coverage of the advanced age interval. Yet, we detect no significant increase in numbers of detected lipids and individual variation with increased age, which was predicted by the metabolic damage accumulation hypothesis of aging [37][38][39]54]. At the same time, increases in metabolite numbers at advanced age were reported in Drosophila [37].…”
Section: Lipidome Changes In Agingcontrasting
confidence: 55%
See 1 more Smart Citation
“…Our study includes 77 samples with ages between 60 and 99 years, 19 of them older than 90, thus providing substantial coverage of the advanced age interval. Yet, we detect no significant increase in numbers of detected lipids and individual variation with increased age, which was predicted by the metabolic damage accumulation hypothesis of aging [37][38][39]54]. At the same time, increases in metabolite numbers at advanced age were reported in Drosophila [37].…”
Section: Lipidome Changes In Agingcontrasting
confidence: 55%
“…Some of the proposed mechanisms of aging predict increases in numbers of detected compounds at advanced age due to metabolic dysfunction and other age-related deregulation [37][38][39]. We detected 10,185 ± 791, 11,203 ± 794, 11,637 ± 909, and 11,912 ± 662 lipids at infant, child, juvenile, and adult stages, indicating a progressive increase in the lipidome complexity of human PFC from infants to adults (ANOVA, P < 0.0001; Fig.…”
Section: Pfc Lipidome Alterations At Advanced Agementioning
confidence: 99%
“…The gut microbiota suffers extensive changes across a lifetime as a result of age, diet, environment, and disease (86,123). A significant body of evidence shows such modifications in the microbiota of model organisms (e.g., flies, fish, mice, and humans).…”
Section: Aging Alters the Microbiotamentioning
confidence: 99%
“…Probiotic diets have been associated with beneficial life span effects in a mouse study 23 , and human centenarians and ultra-centenarians are characterised by a gut microbial composition enriched in health-associated bacteria 24 . Studies in yeast, flies and mice humans have shown that the gut microbiota undergoes dramatic changes during the ageing process 20 , 25 27 , raising the question of whether these changes are a consequence or a cause of ageing. Experimental work in flies showed that, upon ageing, commensal microbes can lead to dysbiosis, which is followed by loss of barrier function and ultimately host demise 28 .…”
Section: Ageing and The Microbiotamentioning
confidence: 99%